High-resolution ground layer turbulence from inside the CFHT dome using a lunar scintillometer. (March 2015) - Pfrommer, T; Hickson, P
Abstract: For ground layer adaptive optics systems, knowledge of the local height- and time- resolved ground layer (GL) turbulence is crucial to link local topography with optical turbulence. Such turbulence profiles have been obtained in the years 2009 and 2010 over 250 hours on Mauna Kea, Hawaii. Results from measurements inside the Canada-France-Hawaii Telescope (CFHT) dome indicate severe degradation of image quality due to a poorly vented dome and thus provide input for dome modifications and design aspects for a new ground layer adaptive optics system. The outside median GL seeing above 6 metres was determined to be 0.48±0.01".